Direitos LGBT: a LGBTfobia estrutural na arena jurídica - Caio Benevides Pedra (2018)
LGBT population faces severe cases of all sorts of exclusion in Brazil, manifested in a number of ways and reflecting in all spheres. In the field of Law, LGBTphobia is so naturalized that it assumes a structural character, contributing to the maintenance and aggravation of the violence and exclusion experienced by those people. In the present work, a diagnosis of structural LGBTphobia in Brazil is presented through the analysis of different concepts, such as gender identity, gender expression, biological sex, and sexual orientation, together with the examination of the historical and current treatment given by Brazilian law to LGBT issues. The role of Law in guaranteeing equal access to the rights that make up citizenship can take various forms, from the proposition of laws to judicial decisions (a field of special development of LGBT rights). The analysis of the national legal system from these concepts, however, leads to the conclusion that Law has quite a difficulty in understanding these realities and in applying basic concepts of sexual diversity and gender in concrete cases. The lack of mastery on these expressions is mainly due to the marginalization of these discussions, which remove from the social domain the evolution of terms and understandings. Thus, the goal of this paper is to discuss these four concepts and analyze how they relate to the legal system and how they have been used by public agents, based on the analysis of laws and jurisprudence associated to the conceptual literature review to facilitate the understanding and the handling of these terms in the reality of the Law.